2004
DOI: 10.1007/s00125-004-1413-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with progression to macroalbuminuria in microalbuminuric Type 1 diabetic patients: the EURODIAB Prospective Complications Study

Abstract: Aims/hypothesis. Type 1 diabetic patients who develop microalbuminuria are clearly disadvantaged in terms of their risk of morbidity and mortality from renal and cardiovascular diseases. It is therefore important to identify potential factors that can predict progression to macroalbuminuria. Methods. This is a 7-year follow-up study of 352 microalbuminuric Type 1 diabetic patients from 31 European centres. Risk factors at baseline were compared in patients who progressed to macroalbuminuria and in patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
109
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 42 publications
11
109
4
3
Order By: Relevance
“…This is in accordance with previous observational studies finding the same association between poor glycaemic control and progression in albuminuria and the rate of progression to DN [20,[22][23][24][25]. In our study, an effort was made to obtain improved glycaemic control by intensive nurse guidance.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with previous observational studies finding the same association between poor glycaemic control and progression in albuminuria and the rate of progression to DN [20,[22][23][24][25]. In our study, an effort was made to obtain improved glycaemic control by intensive nurse guidance.…”
Section: Discussionsupporting
confidence: 93%
“…The increased use of these drugs could be attributed to the additional comments about the current standard management of DN at registration from the study office. Although this study was not an interventional study, these results suggest that the clinicians in the region gradually gained more knowledge on the diagnosis and management of DN throughout the duration of this study.Compared to the results from several studies which that showed the rate of microalbuminuria remission in DN (8,[11][12][13][14][15][16], the rate found in the present study, 27.4%, was not very high. Most of the contributors in this study were general physicians, not diabetes specialists, many previous papers on DN were reported from diabetic specialist faculties, such as, university hospitals or diabetic centers (8,(11)(12)(13)(14)(15)(16).…”
contrasting
confidence: 99%
“…Most of the contributors in this study were general physicians, not diabetes specialists, many previous papers on DN were reported from diabetic specialist faculties, such as, university hospitals or diabetic centers (8,(11)(12)(13)(14)(15)(16). Consequently, our results in this study might accurately reflect the situation of actual clinical practice.…”
Section: Discussionmentioning
confidence: 86%
“…However, this could have been because of lack of power, since triacylglycerol and ApoA-I/ApoA-II and HDL 2 -/HDL 3 -cholesterol ratio predicted progression of renal disease independently of AER when patients with normal AER and microalbuminuria were pooled. In the EURODIAB and Pittsburgh Epidemiology of Diabetes Complications studies, triacylglycerol did not predict the progression to macroalbuminuria [17,28].…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the EURODIAB study included a large number of patients with type 1 diabetes from different parts of Europe and also a much larger number of patients who progressed with respect to their renal disease. It is, however, of note that the patients in the EURODIAB study were recruited between 1988 and 1991, represented 16 different countries with varying diets and undoubtedly represent a rather heterogeneous genetic mixture [16,17].…”
Section: Introductionmentioning
confidence: 99%